The (ir)relevance of the nominal lower bound for real yield curve analysis - Fabian Schupp (European Central Bank (ECB), 2020)
I propose a new term structure model for euro area real and nominal interest rates which explicitly incorporates a time-varying lower bound for nominal interest rates. Results suggest that the lower bound is of importance in structural analyses implying time-varying impulse responses of yield components. With short-term rate expectations at or close to the lower bound, premium components are less reactive to a typical 10 bp increase in inflation, while real rate responses change their sign from positive to negative. However, it is further shown that the lower bound is of only little relevance for decomposing yields into their expectations and premium components once survey information is incorporated. Overall, results support the conclusion that reaching the effective lower bound may change the way macroeconomic shocks propagate along the term structure of nominal as well as real interest rates.
Keywords: E31; E43; E44; E52; 330; Joint real-nominal term structure modelling; lower bound; inflation expectations; inflation risk premium; monetary policy; euro area